Availability of Treatment for Eclampsia in Public Health Institutions in Maharashtra, India - Chaturvedi, Sarika; Randive, Bharat; Mistry, Nerges (Journal of Health, Population and Nutrition, 2013)
Severe pre-eclampsia and eclampsia are common causes of maternal deaths worldwide and more so in developing countries. Magnesium sulphate (MgSO4) is now the most-recommended drug of choice to treat these conditions. Despite favourable policies for the use of MgSO4 treatment in India, eclampsia continues to take a high toll. This study examined the availability and use of MgSO4 treatment in the public health system and poor womens recent experiences with eclampsia treatment in Maharashtra state. A mix of qualitative and quantative methods was used. A facility-based survey of all secondary and tertiary healthcare facilities (n=44) in 3 selected districts and interviews with public and contracted-in private sector obstetricians, health officials, and programme managers were conducted. A list of recently-delivering women from marginalized communities, with up to two livebirths, was drawn through a community-level survey in 272 villages covered by 60 subcentres selected at random. Mothers were selected for interviews, using maximum variation sampling, and interviews were conducted with 17% of the mothers who reported having experienced eclampsia; 61% of facilities had no stock of MgSO4, the stock-out position continuing from a period ranging from 3 months to 3 years while another 20% had some stock, although less than the expected minimum quantity. No treatment for eclampsia was provided in the recent 3 months at 73% facilities. Our survey of recently-delivering mothers recorded a history of eclampsia in 3.2% pregnancies/ deliveries. Interviews with 10 such mothers revealed that treatment for eclampsia has been sought from public as well as private hospitals and from traditional healers. However, facilities where women have received medical treatment are exclusively in the private sector. Almost all public and private care providers were aware of MgSO4 as the gold standard to treat eclampsia; however, it is unclear if they knew of its use to treat severe pre-eclampsia. The private care providers routinely used MgSO4 for eclampsia treatment while the public care providers seemed hesitant to use it fearing risks of complications. We stress the need for improved inventory control practices to ensure sustained availability of supplies and building confidence of care providers in using MgSO4 treatment for severe pre-eclampsia and eclampsia in public facilities, in addition to teaching expectant mothers how to recognize symptoms of these conditions. J HEALTH POPUL NUTR 2013 Mar;31(1):86-95 DOI: http://dx.doi.org/10.3329/jhpn.v31i1.14753